A STUDY OF THE SCIENCE PROGRAMS IN TWELVE IOWA HIGH SCHOOLS. - Winier, Leonard (Science Education, 1957)
The article presents a study of the science programs in twelve high schools in Iowa. The study aimed to establish a closer working relationship with the science teachers in state high schools. In terms of science requirements for graduation, the schools being studied fell into three categories such as general science, general science and biology and one year of any science. The distribution of students enrolled in science courses in all twelve schools includes 39.8 percent in general science, 35.7 percent in biology, 11.3 percent in chemistry, 10.5 percent in physics, 2.2 percent in health and psychology, and 0.5 in consumer science. The study suggests several steps that can be implemented to help improve the status of science teaching in Iowa.